(untitled) (Research, Society and Development, 2022)
Mathematical modeling is a teaching-learning trend that can be used by mathematics teachers who seek to break with traditional teaching. This type of approach, when used, does not consist only of analyzing everyday problems, transcribing them into mathematical language and solving them. It is a process in which, from the models, strategies for action by students can be defined on their reality. For this, it is important that the data used for the elaboration of the models come from the daily life of the students, so that, from the constructed model, important information is removed that allows the decision-making to interfere in reality. The objective of this article is to present a proposal for a mathematical modeling activity, based on critical mathematics education, which can contribute not only to the teaching of linear function, but also to the development of students’ critical and reflective thinking about waste and the importance of the rational use of water in our homes. This is a bibliographical research that presents and discusses the relationship between critical mathematics education and mathematical modeling, within a proposal that is still theoretical, but which can later unfold in more practical and experimental research.